The Impact of Deviation from Optimum Level of Cash Holding on Future Accumulated Abnormal Stock Returns - Mehdi Nazemi Ardkani (Shahid Bahonar University of Kerman, 2016)
The optimum level of cash holdings in a company is the main issue of interest of managers in the recent years. This research concentrates on the effects of deviation from optimum level of cash holding on the future accumulated abnormal stock returns. In this study a sample of 71 companies from Tehran Stock Exchange for the period of 2008 to 2013 was selected. To test the hypotheses, a model of generalized least squares and the panel data method have been used. Results from this study showed that the absolute values of deviation from optimum level of cash holdings do not have negative impact on the cumulative abnormal stock returns. The negative values of deviation from the optimum level of cash holdings lack meaningful relationship with the cumulative abnormal stock returns. The positive values of deviation from the optimum level of cash holdings do not have negative impact on the cumulative abnormal stock returns.